Laporan Kasus: Tantangan dalam Manajemen Epilepsi Katamenial pada Menstruasi Tidak Teratur - Gabriella, Nadia; Kennytha Yoesdyanto (MEDICINUS, 2025)
Introduction: Catamenial epilepsy (CE) is characterized by periodic seizures, defined as ≥2-fold increase in seizure frequency during a specific period of the menstrual cycle. The prevalence of CE ranges from 10 to 70%, affecting over 40% of women with epilepsy. It is particularly prevalent among women with focal epilepsy, especially in cases of temporal lobe epilepsy (TLE). Exacerbation of seizures in CE is attributed to the fluctuations in reproductive steroid levels, which affect neuronal excitability. As of now, there is no definitive treatment available for CE. We reported a case of CE in a female patient with TLE.Case Report: A 20-year-old female patient with irregular periods presented with cluster seizures occurring within three days of her menstrual period. Seizure semiology is described as focal to generalized tonic-clonic seizures, with rightsidelateralization. No neurological deficits were found. Brain magnetic resonance imaging showed no abnormality. The electroencephalogram revealed sharp waves in both left and right temporal lobe. The patient was already treated with phenytoin 400 mg/day. However, due to persistence of seizures during the perimenstrual period, clobazam 20 mg/day was added. Seizure frequency has decreased but the patient remains under close observation.Discussion: The patient has been diagnosed with CE due to the cyclic exacerbation of seizures coinciding with her menstrual cycle. Her seizures consistenly occur within the perimenstrual phase, which is marked by a sudden withdrawal of progesterone and corresponding increase in seizure frequency. The recommended approach involves administering an add-on antiepileptic drug (AED) prior to and during menstruation. However, given the patient’s irregular periods, the mainchallenge lies in determining the optimal timing for this intervention.